Scale Externalities of the G7 Countries - Jürgen Antony (Universität Augsburg, Institut für Volkswirtschaftslehre, 2005)
Scale effects in per capita production are an outcome of many theoretical economic models like second generation growth models, models of the new trade theory or the new economic geography. The prediction is that larger economies should have a higher per capita production than smaller economies. However, in an open economy context the scale of the economy is less important because countries can participate in the scale of other countries through trade. This paper develops an open economy growth model of the second generation type which shows the relevance of the scale of the trading partners in technology goods for per capita production. This model is empirically tested using a cross section of 88 countries for the year 2000. The scale of these economies is measured by a weighted sum of scales of the G7 countries, since these are the countries spending most on R&D and are thus the main origin of technology. The results show that there is a significant effect of this scale variable on per capita production.
urn:nbn:de:bvb:384-opus4-347289
Keywords: F12; F43; O47; 330; Growth and Scale Effects; International Trade